2016
DOI: 10.1097/mnm.0000000000000547
|View full text |Cite
|
Sign up to set email alerts
|

Performance of 177Lu-DOTATATE-based peptide receptor radionuclide therapy in metastatic gastroenteropancreatic neuroendocrine tumor

Abstract: Our data show that high pretherapy F-FDG maximum standardized uptake values were associated with increased chances of treatment refractoriness in GEP-NETs. However, symptomatic improvement was observed in most cases irrespective of grade and F-FDG uptake. High pretherapy F-FDG maximum standardized uptake value in both low-grade and high-grade NET predicted a poor outcome and was associated with disease progression. Introduction of F-FDG-PET/CT parameter as a determinant of response classification increases the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…On the contrary, 18 F-FDG PET seems to have a role in predicting disease progression, tumor response and survival in patients with advanced NETs, treated with PRRT. Most studies suggest that the patients with negative baseline scan may benefit from PRRT more than positive patients, also showing that a high 18F-FDG SUV max is associated with a poor outcome to PRRT and with disease progression [51][52][53]75]. Similar results also emerged in 22 patients with pulmonary NET, evaluated retrospectively [58].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…On the contrary, 18 F-FDG PET seems to have a role in predicting disease progression, tumor response and survival in patients with advanced NETs, treated with PRRT. Most studies suggest that the patients with negative baseline scan may benefit from PRRT more than positive patients, also showing that a high 18F-FDG SUV max is associated with a poor outcome to PRRT and with disease progression [51][52][53]75]. Similar results also emerged in 22 patients with pulmonary NET, evaluated retrospectively [58].…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, other studies reported the possible role of FDG PET in predicting response to PRRT, with only descriptive data. In particular, a high 18 F-FDG SUV max is associated with a poor outcome to PRRT and with disease progression [51,53,75]. This finding also emerged from a retrospective study [58] conducted on 22 patients with pulmonary NET.…”
Section: "Positive Studies"mentioning
confidence: 85%
See 1 more Smart Citation
“…Thapa and his group [53] performed combined imaging using either [ 99m Tc]Tc-Hynic-TOC or [ 68 Ga]Ga-DOTA-TATE scans with [ 18 F]FDG in 50 patients with metastatic GEP-NEN before and after PRRT therapy with [ 177 Lu]Lu-DOTA-TATE. They found that FDG positivity, both in high and in low grade NEN, was associated with a worse response to radionuclide therapy and poor prognosis.…”
Section: Combined [68ga]ga-dota-sst Analogues and [18f]fdg Pet/ct mentioning
confidence: 99%
“…18 F-FDG PET/CT positivity is reported to have therapeutic value in correlating to occurrence of refractoriness to treatment with PRRT with 177 Lu DOTATATE[146]. It also correlates with shorter PFS after PRRT[147] and with shorter postoperative disease-free survival after resection of the NET[148](Table 6).…”
Section: Molecular Imaging In Pannets(table 2) (Fig 1)mentioning
confidence: 99%